1995
DOI: 10.1007/bf00242187
|View full text |Cite
|
Sign up to set email alerts
|

Specific effects of platelet derived growth factor (PDGF) on fetal rat and human dopaminergic neurons in vitro

Abstract: The neurotrophic effects of the BB isoform of platelet-derived growth factor (PDGF) on rat and human fetal mesencephalic dopaminergic neurons have been characterized in vitro. A dose-response analysis demonstrated maximal responses at 30 ng/ml of PDGF-BB. This concentration resulted in a marked increase in the survival and neurite outgrowth from rat and human tyrosine hydroxylase-(TH) positive, presumed dopaminergic neurons after 7 days in vitro. The effects of PDGF-BB on survival of TH-positive neurons were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Interestingly, pre-treatment of neuronal cells with PDGF-BB abrogated neuronal retraction and resulted in reduced cell death compared with cells treated with gp120 alone. PDGF is known to mediate its neuroprotective effect through the induction of neurite outgrowth, as demonstrated in a variety of in vitro neuronal systems, including fetal rat and human dopaminergic neurons (Othberg et al, 1995), SH-SY5Y cells (Hynds et al, 1997) and hippocampal HiB5 cells (Sung et al, 2001). Other neurotrophic factors such as FGF and BDNF have earlier been documented to play a role in rescuing cells against gp120-mediated toxicity (Bachis and Mocchetti, 2005;Hashimoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, pre-treatment of neuronal cells with PDGF-BB abrogated neuronal retraction and resulted in reduced cell death compared with cells treated with gp120 alone. PDGF is known to mediate its neuroprotective effect through the induction of neurite outgrowth, as demonstrated in a variety of in vitro neuronal systems, including fetal rat and human dopaminergic neurons (Othberg et al, 1995), SH-SY5Y cells (Hynds et al, 1997) and hippocampal HiB5 cells (Sung et al, 2001). Other neurotrophic factors such as FGF and BDNF have earlier been documented to play a role in rescuing cells against gp120-mediated toxicity (Bachis and Mocchetti, 2005;Hashimoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Since PDGF-B chain is produced by healthy neurons (Smits et al, 1991) and has neuroprotective properties (Hynds et al, 1997;Mohapel et al, 2005;Othberg et al, 1995;Sung et al, 2001;Tseng and Dichter, 2005), we hypothesized that pre-treatment of neurons with PDGF-BB protein could protect against gp120-mediated neurotoxicity.…”
Section: Protective Effect Of Pdgf-bb Against Gp120 Mediated Neurotoxmentioning
confidence: 99%
“…Comparison of all secreted proteins or proteins predicted to be secreted according to the literature revealed that USSC secrete at least 31 proteins that are known to be involved in neurite growth or axonal regrowth (Table I) including the neurotrophic factors mesencephalic astrocyte-derived neurotrophic factor (MANF) (37), neudesin (38), and neuron-derived neurotrophic factor (NDNF) (39) as well as the growth factors angiopoietin-2 (40), growth/differentiation factor 15 (GDF-15) (41), hepatoma-derived growth factor (HDGF) (42), PDGF (43), and transforming growth factor-beta1/-2 (TGF-␤1/TGF-␤2) (44 -45). Moreover, we identified several matrix-and membrane-associated proteins, e.g.…”
Section: Characterization Of Ussc Secretome By Mass Spectrometry-mentioning
confidence: 99%
“…It is likely that this elevation in PDGF levels is involved not only in the pathogenesis of these conditions but also in the tissue repair processes associated with these diseases. In this regard, it has been shown that PDGF exerts neurotrophic effects on GABAergic and dopaminergic neurons (17,18) and that it protects hip-pocampal neurons against energy deprivation and oxidative injury in vitro (19).…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%